Development and Application of Organic Sonosensitizers in Cancer Therapy - Yuhan Ding; Yuchen Yang; Omer Aras; Feifei An; Mengjiao Zhou; Yichao Chai (Aggregate)
ABSTRACT Sonodynamic therapy (SDT) is an innovative cancer therapy modality that harnesses the energy of ultrasound to activate sonosensitizers for producing reactive oxygen species (ROS), culminating in the eradication of tumor cells. Compared with photodynamic therapy, SDT has the capacity to penetrate deeply into biological tissues, thereby holding significant promise for addressing deeply situated or surgically inaccessible tumors. The effectiveness of SDT is greatly dependent on the characteristics of the sonosensitizers, and unlike inorganic sonosensitizers, organic sonosensitizers offer a more controlled synthesis process and have excellent biocompatibility. This review presents a meticulous undertaking to categorize organic sonosensitizers and elucidate their mechanisms of action and therapeutic effects in the context of SDT. Design strategies for sonosensitizers are also summarized, and we emphasize the critical role of nanotechnology in tumor localization, imaging, and multimodal synergistic therapy, offering an innovative approach for achieving precise tumor targeting. In addition, the synergistic impact of SDT is delineated when integrated with other oncological modalities, such as photothermal therapy and photodynamic therapy, to enhance therapeutic efficacy. Finally, the review also discusses challenges and future perspectives for the advancement of clinical SDT within the realm of oncology.